The peculiarities of functional state changes of cardiovascular system of girls at the age 18-19 years in the process of practicing sport and health tourism - I.A. Denisenko (Physical Education of Students)
The dynamics estimation of the integral indices of cardiovascular system among the female students of higher educational institution during the process of physical education activities, including means of sports and health tourism, has been conducted. There are 40 girls at the age of 18-19 years that participated in the experiment. It is found that by the end of the research the positive decrease of all the types of arterial pressure, coefficient of blood circulation effectiveness, Robinson’s and cardiac indices, common peripheral resistance and significant increase of functional state of cardiovascular system of the organism are being observed among the examined students. There were stated that significantly more optimal cardiac rate indices, systolic, diastolic and average, coefficient of blood circulation effectiveness, Robinson’s index and the level of functional state of organism cardiovascular system (LFSсvs) had been observed among the girls of experimental rather than control group of female students. It is found that the rates of almost all the used indices of cardiovascular system were significantly higher among the students practiced sports and health tourism, than those ones engaged into the traditional program of physical education for higher educational institution. Obtained results certified the sufficiently high effectiveness of using the tourism facilities in optimization of functional state of cardiovascular system among the female students at the age of 18-19 years.